An historical view of the Philippine Islands exhibiting their discovery, population, language, government, manners, customs, productions and commerce - Martinez de Zuniga, Joaquin 1760-1818; Maver, John (J. Asperne [and others] by T. Davison, 1814)
Excerpt from Historia Geográfica, Geológica y Estadística de Filipinas, Vol. 1: Con Datos Geográficos, Geológicos y Estadísticos de las Islas de Luzon, Visayas, Mindanao y Joló; Y los Que Corresponden a las Islas Batanes, Calamianes, Balabac, Mindoro, Masbate, Ticao y Burias, Situadas al N. So. Y S. De Luzon; Isla de Luzon.